2012
DOI: 10.1124/mol.112.081646
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor is a Target of 17-Allylamino-17-demethoxygeldanamycin and Enhances its Anticancer Activity in Lung Adenocarcinoma Cells

Abstract: We have demonstrated that aryl hydrocarbon receptor (AhR) is overexpressed in lung adenocarcinoma (AD). AhR is usually associated with heat shock protein 90 (Hsp90) in the cytoplasm. 17-Allylamino-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…17-AAG, a derivative of geldanamycin, is currently undergoing clinical development as a novel anticancer agent for the treatment of human cancers. It has been reported that 17-AAG could be an effective anticancer drug whether used alone or in combination with other drugs [36,37]. Here we found that 17-AAG decreased HSP90α, then safeguard the activated necroptosis uently.…”
Section: Discussionsupporting
confidence: 61%
“…17-AAG, a derivative of geldanamycin, is currently undergoing clinical development as a novel anticancer agent for the treatment of human cancers. It has been reported that 17-AAG could be an effective anticancer drug whether used alone or in combination with other drugs [36,37]. Here we found that 17-AAG decreased HSP90α, then safeguard the activated necroptosis uently.…”
Section: Discussionsupporting
confidence: 61%
“…17-DMAG is more effective than 17-AAG. It has been shown that 17-DMAG significantly reduced proteins levels of AhR in human lung cancer adenocarcinoma H1355 cells [21] . These results suggested that 17-DMAG-induced dissociation of HSP90 may result in AhR degradation.…”
Section: Discussionmentioning
confidence: 96%
“…The association between AhR and HSP90 has been demonstrated using a sucrose density gradient [16], an immunoprecipitation assay [17], an in vitro ‐translated AhR [14,18], and [ 35 S]‐methionine labeled AhR [15,19]. The influence of HSP90 inhibitor on HSP90 and CYP1A1 protein expression has also been reported using an immunoblot analysis [20], and using cultured lung AD cells [21]. However, there are few reports concerning the direct interaction between the purified AhR and HSP90, because of the difficulty of expressing and purifying AhR.…”
Section: Discussionmentioning
confidence: 99%
“…Although we focused our efforts to uncover the underlying molecular mechanisms in brain metastasis, the dependency of metastatic colonization on HSP90 does not seem to be organspecific. However, whether the potential HSP90-regulated proteins (SRGN, DDA1, UBE4B, GPATCH8, AHR) reflect brain-specific functions of the chaperone remains to be determined as well as their specific molecular dependency on HSP90 since, with the exception of AHR (Chen et al, 2013), the rest have not been previously described to be direct substrates. Furthermore, the ability of four out of five identified targets (AHR, DDA1, UBE4B, GPATCH8) to translocate to the nucleus (Cheng et al, 2017;Du et al, 2016;Murray et al, 2014) where they could regulate mechanisms required for brain colonization is currently being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, among the top five downregulated proteins (Fig. 5 D), only AHR has been functionally linked to HSP90 (Chen et al, 2013), which could suggest the presence of HSP90-related biological programs independent of the well-established cancer-related HSP90 clients (Whitesell and Lindquist, 2005). In addition, four top downregulated proteins (AHR, UBE4B, DDA1 and GPATCH8 (G patch domain-containing protein 8)) have been shown to be able to translocate into the nucleus (Cheng et al, 2017;Du et al, 2016;Murray et al, 2014) and 50% of top downregulated signatures belong to nuclear signaling pathways (Fig.…”
Section: Patient-derived Organotypic Cultures (Pdoc) Are Sensitive Tomentioning
confidence: 99%